BIBLIOMETRIK STUDI TENTANG KONSELING ISLAM DALAM MENDUKUNG KARIR IBU RUMAH TANGGA BERPENDIDIKAN - Harahap, Nurintan Muliani; Siti Wahyuni Siregar (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
This research aims to understand the role of Islamic counseling in supporting the careers of educated housewives who play dual roles as mothers and workers. The issue raised is how Islamic counseling helps women face the challenges of balancing career and family life. The research objectives also include how such counseling impacts women's emotional and psychological well-being. The method used is a qualitative approach with bibliometric analysis. Data were collected through a literature search from the Scopus and Google Scholar databases, producing 34 relevant articles based on keywords such as "Islamic counseling," "career," and "housewife." The research results show that Islamic counseling helps women manage multiple roles, reduces stress, and strengthens family relationships. The interesting fact is that this spiritual-based counseling not only helps in the emotional aspect, but also supports balance between career and family. The implication of this research is the importance of Islamic counseling as part of services to help women who play dual roles